Expectations and Comparison to other Destinations: Tourists’ visiting KwaZulu-Natal in South Africa: Array - Ezeuduji, Ikechukwu O.; Mlambo, Sinolwazi S. (EuroEconomica, 2020)
This study assessed tourists’ judgements of the destination KwaZulu-Natal compared to expectations and other destinations. A structured questionnaire survey of 406 tourists in this destination yielded data for statistical analysis. Results show that tourists visiting KwaZulu-Natal mostly underpin this destination’s favourable competitiveness on its comfortable weather conditions, strong sense of humanity, unique and diverse attractions and activities, and capability to provide visitors with new knowledge and authentic visitor experience. This study recommends that Tourism KwaZulu-Natal - the Destination Management Organisation, should try to improve on the cleanliness of the destination, the efficiency of its local transport services, and the destination’s safety and security.